Ligand-based design of GLUT inhibitors as potential antitumor agents. Issue 7 (1st April 2020) - Almahmoud, Suliman; Jin, Wei; Geng, Liying; Wang, Jing; Wang, Xiaofang; Vennerstrom, Jonathan L.; Zhong, Haizhen A.
Graphical abstract: Abstract: Glucose transporters (GLUTs) regulate glucose uptake and are often overexpressed in several human tumors. To identify new chemotypes targeting GLUT1, we built a pharmacophore model and searched against a NCI compound database. Sixteen hit molecules with good docking scores were screened for GLUT1 inhibition and antiproliferative activities. From these, we identified that compounds 2, 5, 6 and 13 inhibited the cell viability in a dose-dependent manner and that the IC50 s of 2 and 6 are<10 µM concentration in the HCT116 colon cancer cell line. Lead compound 13 (NSC295720) was a GLUT1 inhibitor. Docking studies show that GLUT1 residues Phe291, Phe379, Glu380, Trp388, and Trp412 were important for inhibitor binding.